Investigation of diuretic activity of 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles’ derivatives - O. A. Suhak; O. I. Panasenko; Ye. G. Knysh; A. A. Safonov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
It should be noted, that the clinical and therapeutic effect of diuretic drugs is not necessarily associated with an increase diuresis. So, for example, diuretics are also prescribed as a means of dehydration emergency therapy for pulmonary edema, brain, in the integrated therapy of patients with arterial hypertension, with glaucoma, epilepsy, as well as for induction of forced diuresis in poisoning. Therefore, the search for new diuretic agents among heterocyclic systems can solve the problem of treating a complex of diseases of different genesis. The aim of this work was to study the diuretic activity of 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole derivatives. Materials and methods. The method of E. B. Berchin was used to establish the influence of synthesized compounds on the excretory function of the kidneys. All compounds for this research have been synthesized at the Toxicological and Inorganic Chemistry Department of ZSMU. Results and discussion. Diuretic activity of 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives was investigated. Some regularities between “structure – activity” were established: the replacement of the phenyl radical in the 4-phenyl-5-(thiophen-2- ylmethyl)-4H-1,2,4-triazole-3-thiol molecule with ethyl or methyl leads to a slight increase in diuretic effect. The introduction of alkyl radical to 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triasole-3-thiol molecule results in diuretic effect increase. The introduction of 2-chloro-6- fluorobenzyl, 4-hydroxybenzyl and 3,5-dimethoxybenzyl radical to N’-R1 -iden-2-((4-methyl-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl) thio)acetohydrazide molecule also results in diuretic activity increase. Replacement of 3,4-difluorobenzyl radical with 4-fluorobenzyl, 2-bromobenzyl, 2-hydroxybenzyl to N’-R1 -iden-2-((4-phenyl-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetohydrazide molecule results in diuretic activity decrease. Conclusions. The diuretic activity of 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles derivatives was established by the method of Ye. B. Berchin. The derivatives of 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles exhibit both diuretic and antidiuretic effects. Some relationship between “structure – activity” was established. The most active compound was 3-(heptylthio)-4-methyl-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole.